X-linked adrenoleukodystrophy: Clinical review and case report (International Seven Journal of Health Research, 2024)
Introduction: Adrenoleukodystrophy is a rare, recessive, hereditary genetic disease, linked to the X chromosome, with degenerative and incurable characteristics, which preferentially affects males. It directly affects the non-development of the adrenal/suprarenal glands and the white matter of the brain due to the accumulation of long-chain fatty acids in these sites, causing destabilization of the myelin sheath and affecting the transmission of nerve impulses. Objective: The aim of this study is based on the scarcity of literature on this rare pathology, which affects around 1:15,000 to 25,000 individuals, in an attempt to portray the clinical course of this disease. Case presentation: A 34-year-old male patient, diagnosed with X-linked adrenoleukodystrophy following an investigation into the death of his 13-year-old brother with the disease, has been under multidisciplinary follow-up since diagnosis, with genetics, endocrinology, neurology and psychology teams, undergoing annual consultations and control laboratory tests, as well as a brain MRI. At the age of 19, she informed us that she did not wish to have a bone marrow transplant. She has been followed up clinically ever since. Discussions: The diagnosis can be made in prenatal tests, the gold standard score for grading the pathology is the LOES score, totaling 34 points, according to the patient's score, it is possible to see if they will benefit from treatment.